Effect of Chemical Fertilizers on the Efficiency of Biochar in Reducing Lead Mobility in Soil - Chompoonut Chaiyaraksa; Chaiyasit, Kanokwan (Science & Technology Asia, 2024)
The objective of this research was to investigate the impact of ten different fertilizers on the mobility of lead in soils that had been treated with biochar. The soil used in this study was collected from Chanthaburi Province. To simulate the experimental conditions, this soil was artificially enriched with 550 mg/kg of lead. The synthetic soil was prepared by mixing it with 10% biochar and 0.04% of various chemical fertilizers. To assess the bioavailability of lead in the soil to plants, an extraction process using diethylenetriamine pentaacetate was performed. This allowed researchers to determine how these fertilizers affected the movement and availability of lead in the soil for plant uptake. In the study, it was observed that among the fertilizers tested, urea was the only one that increased the bioavailability of lead in the soil, making it more accessible to plants. Sequential extraction techniques were employed to analyze six different forms of lead in the soil. Interestingly, all fertilizers, except for urea, caused a transformation of lead from less stable forms to more stable forms in the soil. To further investigate the relationship between fertilizer variables and heavy metal uptake, a stepwise linear regression analysis was applied. The results indicated that the mobility of lead in the soil was primarily influenced by the nitrogen content, potassium levels, and sulfate ion concentration in the fertilizers.